2005
DOI: 10.1021/ja0436291
|View full text |Cite
|
Sign up to set email alerts
|

Superacidifiers: Assessing the Activation and the Mode of Charge Transmission of the Extraordinary Electron-Withdrawing SO2CF3and S(O)(NSO2CF3)CF3Substituents in Carbanion Stabilization

Abstract: We report on a structural (multinuclear NMR), thermodynamic (pK a), and kinetic (Marcus intrinsic reactivity) study of the ionization of benzylic carbon acids activated by an exocyclic (α) SO2CF3 group and SO2CF3 or S(O)(NSO2CF3)CF3 in the para position of the phenyl ring. The latter exerts an enormous acidifying effect of ca. 8 pK units as compared with 4-H benzyltriflone in Me2SO solution, (corresponding to remarkably high Hammett σ values σp ≈ 1.35, σp - ≈ 2.30). In considering the origin of this effect, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 61 publications
(110 reference statements)
6
27
0
1
Order By: Relevance
“…(3)]. Promising approaches to elucidate the magnitude and origin of intrinsic barriers as described by Bernasconi, [172] Bordwell, [173] Hoz, [23] Kreevoy, [20d] Lewis, [174] Murdoch, [175] Richard, [16a] and Terrier [176] should, therefore, be further developed.…”
Section: Discussionmentioning
confidence: 99%
“…(3)]. Promising approaches to elucidate the magnitude and origin of intrinsic barriers as described by Bernasconi, [172] Bordwell, [173] Hoz, [23] Kreevoy, [20d] Lewis, [174] Murdoch, [175] Richard, [16a] and Terrier [176] should, therefore, be further developed.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the replacement of NO 2 by SO 2 CF 3 is accompanied by an appreciable decrease in intrinsic reactivity ( log k o = −0.70). This is certainly a reflection of the preferential stabilization of the negative charge of the transition state by a para-SO 2 CF 3 group [28,29]. On the other hand, a recent study of the σ -complexation of 1a and 1b and other anisole series 2,4,6-trinitro-and 4-SO 2 CF 3 -2,6-dinitro-has revealed that the especially high capacity of resonance stabilization of the negative charge of the adducts through an Fπ -type polarization effect is a major factor that accounts for the strong activation provided by SO 2 CF 3 groups [4].…”
Section: Intrinsic Reactivity Of Triflonesmentioning
confidence: 99%
“…(3)]. Vielversprechende Ansätze, die Größe und den Ursprung intrinsischer Barrieren zu ermitteln, wie von Bernasconi, [172] Bordwell, [173] Hoz, [23] Kreevoy, [20d] Lewis, [174] Murdoch, [175] Richard [16a] oder Terrier [176] beschrieben, sollten daher weiterentwickelt werden. …”
Section: Ambidente Elektrophileunclassified